What’s the protocol? Canadian university research ethics boards and variations in implementing Tri-Council policy - Karram Stephenson, Grace; Jones, Glen A.; Fick, Emmanuelle; Bégin-Caouette, Olivier; Taiyeb, Aamir; Metcalfe, Amy (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2020)
This article is concerned with the differences in REB policy and application processes across Canada as they impact multi-jurisdictional, higher education research projects that collect data at universities themselves. Despite the guiding principles of the Tri-Council Policy Statement 2 (TCPS2) there is significant variation among the practices of Research Ethics Boards (REBs) at Canada’s universities, particularly when they respond to requests from researchers outside their own institution. The data for this paper were gathered through a review of research ethics applications at 69 universities across Canada. The findings suggest REBs use a range of different application systems and require different revisions and types of oversight for researchers who are not employed at their institution. This paper recommends further harmonization between REBs across the country and national-level dialogue on TCPS2 interpretations.